Psychological Happiness among Sultan Qaboos University Students in Oman - Manal K. Al Fazari (Sultan Qaboos University, 2017)
The aim of this research was to investigate the relation of psychological happiness of Sultan Qaboos University students with some variables using a specific questionnaire that was designed for the purpose of this study. It consisted of 36 items that represent 3 dimensions (personal aspect, academic aspect, and social aspect). The sample included 490 male and female students from all the university colleges (2016-2017 academic year enrolments). The Cronbach's alpha coefficient of the questionnaire was .84. The findings show that the majority of the students expressed a medium level of happiness (69.8%). Significant relationships between the psychological happiness and gender and type of residence (on-campus, off campus) were found. However, age, college and region did not significantly correlate with students' psychological happiness.